Faculty development for interprofessional education in resource-constrained West Africa: priorities, institutional gaps and implementation pathways - Abena Agyarkowa Otchere-Darko; Amrita Sarkar; Debjit Roy (International Journal Of Community Medicine And Public Health, 2026)
Background: Interprofessional education (IPE) is a recognized strategy for addressing healthcare workforce challenges in sub-Saharan Africa, but evidence on faculty preparation in resource-constrained settings is limited. Methods: Between September and November 2024, we conducted a cross-sectional needs assessment of all eligible faculty (n=28; 100% response) at a West African regional medical education and research institute. A validated, pilot-tested semi-structured questionnaire (content validity index 0.89; Cronbach’s α=0.82) assessed demographics, professional development priorities, institutional support, and programme-design preferences. Quantitative data were summarised using frequencies, percentages, weighted priority scores, and five-point Likert means; open-ended items underwent thematic analysis. Results: Most participants held master’s degrees (67.9%, n=19); 60.7% were female, 50.0% held lecturer rank, and 78.6% had under ten years’ teaching experience. Research methodology (85.7%) and data analysis (89.3%) were the top development priorities. Enhanced mentorship was the highest improvement priority (92.9%; mean 4.3/5), yet only 28.6% currently accessed formal mentorship programmes. Institutional support ratings were modest (grand mean 3.1/5), with professional development rated lowest (mean 2.8/5). Key programme characteristics identified were institutional leadership support (89.3%), research-practice integration (85.7%), resource allocation (82.1%), collaborative learning (78.6%), flexible delivery (75.0%), and comprehensive assessment (71.4%). Faculty preferred quarterly delivery (50.0%) in blended formats (75.0%), and 89.3% reported readiness to participate. Conclusions: A pronounced gap exists between faculty demand for mentorship and existing institutional provision. Research-integrated, blended faculty development anchored in formal mentorship is a feasible, contextually appropriate approach to strengthen IPE capacity at this institution; broader generalisability requires multisite investigation.